REALIZING THE ACTIVE ROLE OF YOUTH IN INCLUSIVE DEVELOPMENT THROUGH CO-PRODUCTION: A STUDY OF THE SAMIN COMMUNITY IN JEPANG HAMLET, MARGOMULYO, BOJONEGORO REGENCY - Sulikah Asmorowati; Jusuf Irianto; Violeta Schubert; Mary Mangai; Wilujeng Dwi Windhiari; Saskia Intandivanty Kamalia Anggika (Dialogue : Jurnal Ilmu Administrasi Publik, 2025)
Inclusive development encompasses social, environmental, and current generational development (Gupta et al., 2015). In this effort, all community groups must be actively involved, including youth within Indigenous communities. The Samin community is an Indigenous group whose principles support inclusive development. However, the role of youth in this context remains underexplored and requires further investigation. Therefore, this qualitative study aims to examine the role of youth in promoting inclusive development within the Samin Indigenous community. Data were collected through observation, in-depth interviews, and focus group discussions (FGDs). The findings revealed that youth participation in inclusive development remains limited. Consequently, strategic measures are needed to raise awareness among elders to involve youth, the presence of the Samin Cultural Gallery as a learning resource, and expanded networks to strengthen governance and tourism management, which positively affects the local economy